Isolation and evolutionary analyses of porcine epidemic diarrhea virus in Asia - Liang, Wan; Zhou, Danna; Geng, Chao; Yang, Keli; Duan, Zhengying; Guo, Rui; Liu, Wei; Yuan, Fangyan; Liu, Zewen; Gao, Ting; Zhao, Ling; Yoo, Dongwan; et al. (PeerJ, 2020)
Porcine epidemic diarrhea virus (PEDV) is a leading cause of diarrhea in pigs worldwide. Virus isolation and genetic evolutionary analysis allow investigations into the prevalence of epidemic strains and provide data for the clinical diagnosis and vaccine development. In this study, we investigated the genetic characteristics of PEDV circulation in Asia through virus isolation and comparative genomics analysis. APEDV strain designated HB2018 was isolated from a pig in a farm experiencing a diarrhea outbreak. The complete genome sequence of HB2018 was 28,138 bp in length. Phylogenetic analysis of HB2018 and 207 PEDVs in Asia showed that most PEDV strains circulating in Asia after 2010 belong to genotype GII, particularly GII-a. The PEDV vaccine strain CV777 belonged to GI, and thus, unmatched genotypes between CV777 and GII-a variants might partially explain incomplete protection by the CV777-derived vaccine against PEDV variants in China. In addition, we found the S protein of variant strains contained numerous mutations compared to the S protein of CV777, and these mutations occurred in the N-terminal domain of the S protein. These mutations may influence the antigenicity, pathogenicity, and neutralization properties of the variant strains.
Keywords: Porcine epidemic diarrhea virus; Virus isolation; Genetic evolutionary analysis; Amino acid mutations; Asia